Aspergillus system properties and applications - Gupta, Vijai Kumar (Saint Louis : Elsevier Science, 2016)
New and Future Developments in Microbial Biotechnology and Bioengineering: Aspergillus System Properties and Applications provides information on emerging issues related to recent advancements in aspergillus research and its applications in bioprocess technology, chemical engineering, genome biology, molecular taxonomy, secondary and metabolite production, industrial process and biofuels/bioenergy research, and alternative fuel development. The book covers the various novel enzymes secreted by these fungi and their specific use in the food, textile, pulp and paper, biocellulosic ethanol production, and other industries. The book describes research and experimentation on aspergillus activity and directly connects them to their use in bioprocess technology, chemical engineering, bioremediation process, secondary metabolite production, pharmaceutical processes, protein production, industrial process, biofuels/bioenergy research, and alternative fuel development. Readers will find this book to be an indispensable resource for biotechnologists, biochemical engineers, biochemists, microbiologists, bioinformatics researchers, and other biologists who are interested in learning about the potential applications of these fungi.
Looking for Protease-Deficient StrainsHuman Proteins Expressed in Aspergillus; Synthetic Biology as an Innovative Approach for the Biosynthesis of Novel Compounds; Bioremediation; References; 5 Aspergillus Secretome: An Overview; Introduction; Secretome; Access to Secretome; Genomic Analysis; Proteomics Approach; Bioinformatics Approach; Genomic Analysis; Proteomics Approach; Bioinformatics Approach; Recent Breakthroughs; Genomics; Proteomics; Bioinformatics; Conclusion; References; III. Secondary Metabolism; 6 Secondary Metabolism and Antimicrobial Metabolites of Aspergillus; Introduction.
Print version record.
Metabolites.
Keywords: Microbial biotechnology; Biotechnological microorganisms; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Biotechnological microorganisms; Microbial biotechnology; Electronic books